MITIGATING PULSE DISTORTION IN OPTICAL FIBERS USING DIGITAL BACKPROPAGATION AND DISPERSION MANAGEMENT - Lawan, Sani Halliru (FUDMA JOURNAL OF SCIENCES, 2025)
This research investigates the propagation effects of optical pulses traveling through fiber links, focusing on phase modulation, nonlinear phase change, and pulse broadening. We analyze these phenomena to enhance the performance of optical communication systems by evaluating key metrics such as nonlinear phase change (in degrees, o) and pulse broadening ratio over propagation distances. Our findings underscore the significant role of nonlinearities in pulse distortion and assess the effectiveness of Digital Backpropagation (DBP) and optimal dispersion techniques in mitigating these impairments. Simulation results demonstrate that DBP is more effective than optimal dispersion management, reducing nonlinear phase change by maintaining it at 15o up to 80 km, compared to optimal dispersion management, which stabilized it to 34o after the initial peaks before the interaction length, defined as the distance over which nonlinear effects manifest. Similarly, DBP achieves complete suppression of pulse broadening, maintaining the ratio at 1:1 up to 80 km. In contrast, optimal dispersion management only achieves lowering the ratio to 40:1. These findings highlight that DBP has superior capability in mitigating both nonlinear phase change and linear pulse broadening, significantly enhancing signal fidelity over long distances and offering valuable insights for the design and optimization of next-generation optical networks.